Estudio de los mecanismos de regulación de la proteína asociada a resistencia a multidrogas 4 (MRP4) y sus implicancias en adenocarcinomas ductales pancreáticos - Carozzo, Alejandro Enrique (2015)
Pancreatic ductal adenocarcinoma (PDAC), the most common histological subtype of pancreatic cancer, is one of the most lethal human cancers, representing the fourth leading cause of cancer-related death in developed countries. In this type of neoplasm and its previous injuries, several components of the cAMP signaling pathway are frequently altered. Due to the lack of effective therapies for this pathology, there is an urgent need to search and validate new therapeutic targets and biomarkers for early detection.\nIn this thesis, we demonstrate that the MRP4-mediated cAMP extrusion plays a critical role in cell proliferation of PDAC, resulting from the participation of this cyclic nucleotide in a mitogenic circuit involving specific receptors on the plasma membrane.\nOur results also indicate that cAMP regulates MRP4 transcription through a dual mechanism, in which the balance between the intra- and extracellular levels of this second messenger plays a key role in this transporter expression. Therefore, the experimental results described in this thesis, in addition with the bibliographic reports analyzed, provide evidence as to propose the MRP4-mediated cAMP extrusion process as a new potential target for PDAC therapy.